Development of a loop-mediated isothermal amplification assay for sensitive and rapid detection of toxigenic vibrio cholerae - Engku Abd Rahman , Engku Nur Syafirah (2017)
Cholera is known as significant public health problem worldwide which is caused by toxigenic Vibrio cholerae. Currently, the routine cholera diagnosis involves bacterial culture and biochemical tests but conventional methods are time consuming,inefficient, laborious and skilled personnel is required to perform the tasks. Until now, no rapid molecular diagnostic kits commercially accessible that can be used in laboratory and field settings. Consequently, this study was focused on developing a multiplex LAMP assay for detection of cholera that is simple, fast and highly sensitive. The designed primers were constructed for the detection of toxigenic gene, ctxA that presents only in toxigenic strains of V. cholerae and one internal control (SSP2). BLAST search analyses were used to confirm the primers specificity and the same primers were also tested on other non-Vibrio bacterial strains to ensure that the target gene is highly specific. The reliability of LAMP assay to rule out false negative result was validated with the inclusion of an internal control. The optimised thermostabilised multiplex LAMP assay consists of dry and wet format. For dry format, the components were 0.6 mM dNTPs mixture, 1.6 pmol/ μl of each FIP and BIP for both target and internal control, 0.8 pmol/ μl of LB and LF for both target and internal control, 0.2 pmol/ μl of each F3 and B3 for both target and internal control, 4.27 U/ μl of Bst 2.0 WarmStart DNA polymerase and enzyme stabiliser combinations selected (8% trehalose + 0.25 mg/ ml BSA + 6% FICOLL) with 0.05% Orange G loading dye. The wet format composed of 1X LAMP amplification buffer,6 mM MgSO4, and 0.4 M betaine and kept as aqueous buffer. A 13.3 pg/ μl of SSP2 plasmid DNA was integrated in each run which functions as internal control. The thermostabilised multiplex LAMP was tested for accelerated stability test at 25 and 37℃ for 1 month. Results showed that the thermostabilised multiplex LAMP mixture stored at 25 and 37 ℃ was stable until 1 month. After calculation of accelerated heat stability test, it can last at room temperature for 3.14 months in correlation with 37 ℃ storage. The multiplex LAMP assay results obtained showed 100% specific with 73 V. cholerae strains only and not for 5 Vibrio species and 37 non-Vibrio strains. The analytical sensitivity of the multiplex LAMP assay at genomic level was 100 fg/ μl whereas at bacterial level, the limit of detection was found to be 102 CFU/ ml, respectively. The developed thermostabilised multiplex LAMP assay is fast and distinctly sensitive and specific for the recognition of toxigenic V. cholerae. This assay has potential to be implemented during cholera outbreak and consequentially helpful in reducing the morbidity and mortality of cholera cases.